Pendekatan Pemberdayaan Ekonomi Berbasis Komunitas Melalui Pelatihan Pembuatan Sabun Mandi Beraroma Kopi - heri, Ignatius; Josephine Tyra, Maria; Lina, Lina; Riyanto, Agustinus; Gunady Ony, Johan; Fernando, Agustinus (Universitas katolik Musi Charitas, 2022)
The current trend of the digital era gives an indication of opportunities for community economic empowerment. Through data on the increase in the percentage of internet and social media users in Indonesia, justification is made for the formation of an interactive-transactional activity system. In this system, individuals are socially bound to share information and knowledge. This is the basis of a community-based economic empowerment approach where the interactive-transactional activity system in the collective formation is “intervened” through various activities of economic value to form the socio-economic capital of the community. This approach was used by the Community Service Team of the Musi Charitas Catholic University in Palembang through the “Training for Making Coffee-Scented Bath Soap” with 50 (fifty) community partners affiliated with a Catholic Church socio-religious organization in Banyu Urip Village, Tanjung Laga District. , Banyu Asin Regency, South Sumatra. The results of the activity are in the form of increasing: (1) Awareness of individual participatory and contributing in organizational membership (social aspect); (2) the capacity of creativity to find new objects of economic value (creative economic aspects), and ; (3) Commitment to share knowledge that is directed to the formation of social capital for creative communities (socio-economic aspects).